KARAKTERISTIK PERMAINAN BOLAVOLI TIM PUTERA DAN TIM PUTERI (STUDI PADA PROLIGA 2012 DI GRESIK) - HENDRO SUSANTO, DWI Hendro (Jurnal Prestasi Olahraga, 2013)
The purpose of this study was to obtain empirical data on the characteristics of male and female team?s on Proliga 2012 in Gresik. In the championship, there are some differences on the characteristics of the pattern which is made by all of teams. The characteristics are included duration of time, serve, passing, set-up, smash and block. The type of this research was quantitative research by using descriptive analysis method. The data were obtained from the entire game on Proliga 2012 in Gresik. It was conducted observationally. The results of the characteristics of male and female team?s volley ball game on Proliga 2012 in Gresik, they are: (1.a) The average time that is needed in one game from all of the games is male team that is faster than female team , (1.b) The total average of male team in each set is faster than female team, (1.c) The total time on rally includes: i) Started from effective serve to hit till the ball dead, male team is faster than female team, ii) Started from effective whistle till the ball dead, male team is faster than the female team, (1.d) The total average time of clean rally and dirty at the male team is faster than female team, (1.e) The total time of the game with the score 3-0, 3-1, and 3-2, male team is faster than female team, (2.a) The total average offensive team in every rally is 46% for male and 54% female team, (2.b) The total of jumping activity of male team is faster than female team, (3.a) The male team often serve jump technique than female team, (3.b) The female team more often do the passing movement when receive or dig than the male team, (3.c) The female team more often stem by using smash with two blockers, while the male team more often stem block with three blockers , (3.d) the feed of down passing with the technique still uses by a team of female than male team. It can be concluded that characteristics of male and female team?s volley ball game on Proliga 2012 are the different. Keywords: characteristics, volleyball, male team, female team